The development and standardization of speech test material in English for Indians - KC, Swarnalatha (Journal of All India Institute of Speech and Hearing)
Speech audiometry is an ilnportant element in the battery of audiolnetric tests. It has come into existence because of some inherent disadvantages in pure-tone audiometry. Though pure-tones are physically and mathematically simple and are easy to present, they are relatively uncommon and unimportant. Moreover pure-tone audiometry does not provide information about the person’s ability to hear above the threshold. On the other hand speech audiometry helps in earlier detection of slight losses otherwise overlooked and provides better documentation of initial and slight going after therapy.